2018
DOI: 10.1029/2018gl077837
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Present and Future European Temperature Extremes on the Location of Atmospheric Blocking

Abstract: The impact of atmospheric blocking on European heat waves (HWs) and cold spells (CSs) is investigated for present and future conditions . A 50‐member ensemble of the second generation Canadian Earth System Model is used to quantify the role of internal variability in the response to blocking. We find that the present blocking‐extreme temperature link is well represented compared to ERA‐Interim, despite a significant underestimation of blocking frequency in most ensemble members. Our results show a strong corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 38 publications
(78 reference statements)
7
87
0
Order By: Relevance
“…This high validation error could result from “false alarms” (blockings without extreme) and “missed events” (extremes without blocking). Looking at a few cases of false alarms, we find that most of them are blockings over ocean, which is not surprising because we count surface hot extremes only over continents, and that blockings have stronger local impact than remote impact when it comes to hot extremes (Brunner et al, ; Röthlisberger et al, ). For missed events, we will see an example in section .…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…This high validation error could result from “false alarms” (blockings without extreme) and “missed events” (extremes without blocking). Looking at a few cases of false alarms, we find that most of them are blockings over ocean, which is not surprising because we count surface hot extremes only over continents, and that blockings have stronger local impact than remote impact when it comes to hot extremes (Brunner et al, ; Röthlisberger et al, ). For missed events, we will see an example in section .…”
Section: Resultsmentioning
confidence: 77%
“…Such factors need to be considered in future work. However, Schaller et al () and Brunner et al () found no significant change in the blocking‐heat wave link in the future under Representative Concentration Pathway 8.5, though these studies come with the caveat of a strong underestimation of blocking in the used models. One may also consider a strong blocking‐extreme link for the present day as a necessary but not sufficient condition for using changes in blocking to predict changes in weather extreme in a future climate.…”
Section: Introductionmentioning
confidence: 93%
“…Three points regarding our methodology should be kept in mind. First, the threshold for identifying hot spells is slightly lower than that used in other studies (Brunner et al, ; Sillmann et al, ). However, the average T2mmax anomaly during hot spells defined by our approach ranges from +4 to +7 K over most land areas (Figure S3), which illustrates that these periods are indeed rather hot.…”
Section: Methodsmentioning
confidence: 91%
“…Over the past decade, various studies have established a link between atmospheric blocking and different weather situations (e.g., Sillmann and Croci‐Maspoli, ; Brunner et al . ; Sousa et al . ; Woollings et al .…”
Section: Introductionmentioning
confidence: 97%